Mengurangi Defect Saat Proses Loading dengan Pendekatan Six Sigma DMAIC di Warehouse PT. Mulford Indonesia - Muhammad Nurhasan Assidiq; Ismail Kurnia; Algi Hayatul Firman; Florida Butarbutar; Syarif Hadiwijaya (Jurnal Teknik Ibnusina, 2026)
The objective of this research is to improve the causes of product damage in Alderon 830 during the loading process at PT Mulford Indonesia using the Six Sigma DMAIC (Define, Measure, Analyze, Improve, Control) approach. The analysis reveals four major types of defects, namely scratches, dents, holes, and center breakage. Scratches are the most frequently encountered defect. This study integrates the methods of 5W+1H, SIPOC, CTQ, DPMO, capability process, fishbone diagram. The research findings indicate that human factors, environment, method, material, and machine contribute to product damage. The aim of this research is to propose seven improvements, including enhanced direct supervision, reduction in custom production, improved coordination with suppliers, implementation of product labeling, proper storage positioning, monthly stocktaking supervision, and better forklift maintenance. The implementation of these improvements resulted in a decrease of 0.70% in the percentage of damage and an increase in sigma from 3.61 to 3.65. The research findings demonstrate the effectiveness of the Six Sigma DMAIC approach in identifying and rectifying the causes of product damage in Alderon 830.